A phage cocktail combined with the enteric probiotic Lactobacillus reuteri ameliorated mouse colitis caused by S. typhimurium. Issue 16 (25th July 2022) - Wang, Xinwu; Ji, Yalu; Qiu, Cao; Zhang, Hao; Bi, Lanting; Xi, Hengyu; Lei, Liancheng; Liu, Bing; Han, Wenyu; Gu, Jingmin
Abstract : Salmonella enterica serovar Typhimurium ( S. typhimurium ) is one of the most important foodborne pathogens that causes colitis in humans. Abstract : Salmonella enterica serovar Typhimurium ( S. typhimurium ) is one of the most important foodborne pathogens that causes colitis in humans. In this study, we compared the effects of a therapeutic treatment using a phage cocktail (Pc) in combination or not with Lactobacillus reuteri ( L. reuteri ) in an S. typhimurium -induced colitis murine model. An oral administration of 4 × 10 8 CFU per mouse of S. typhimurium resulted in intestinal barrier disruption and severe inflammatory symptoms. S. typhimurium in the colon of the mice treated with the Pc and L. reuteri (PcLR) combination were completely removed compared to those in the single Pc or single L. reuteri treatment groups. Furthermore, compared with the infected group, the intestinal barrier and colonic pathological damage were significantly improved in the PcLR-treated group. Additionally, the short-chain fatty acid (SCFA) levels in the feces of the mice in the PcLR treatment group were significantly increased compared to those in the feces of the mice in the infected group. In addition, the combination of Pc with acetate and reuterin released by L. reuteri (PcReAc) can also achieve the same effect as PcLR treatment. Thus, these results indicated that the acetate and reuterin released by L. reuteri play an important role in the treatment. The extraordinary therapeutic effects of PcLR and PcReAc depend on the specific bactericidal activity of Pc and the broad-spectrum bactericidal activity and immunomodulation of L. reuteri (or acetate and reuterin) in the host. This study provides a new concept for the treatment of inflammatory diseases caused by intestinal pathogens.